2018
DOI: 10.1111/tpj.13929
|View full text |Cite
|
Sign up to set email alerts
|

Apple SRNase interacts with an actin‐binding protein, MdMVG, to reduce pollen tube growth by inhibiting its actin‐severing activity at the early stage of self‐pollination induction

Abstract: In S-RNase-mediated self-incompatibility, S-RNase secreted from the style destroys the actin cytoskeleton of the self-pollen tubes, eventually halting their growth, but the mechanism of this process remains unclear. In vitro biochemical assays revealed that S-RNase does not bind or sever filamentous actin (F-actin). In apple (Malus domestica), we identified an actin-binding protein containing myosin, villin and GRAM (MdMVG), that physically interacts with S-RNase and directly binds and severs F-actin. Immunofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…As one of the woody perennial species, the apple tree often suffers from a variety of environmental stresses making it urgent to comprehend the function of the CIPK genes in stress responses in order to improve crop tolerances against adverse environments [ 27 ]. In this study, all the CIPK genes were identified by apple genome-wide analysis, their evolutionary relationship phylogenetically was evaluated, and their structure and chromosomal distribution of the CIPK genes were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the woody perennial species, the apple tree often suffers from a variety of environmental stresses making it urgent to comprehend the function of the CIPK genes in stress responses in order to improve crop tolerances against adverse environments [ 27 ]. In this study, all the CIPK genes were identified by apple genome-wide analysis, their evolutionary relationship phylogenetically was evaluated, and their structure and chromosomal distribution of the CIPK genes were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…The authors speculated that S-RNase simultaneously decrease Ca 2+ current and inhibit ROS formation; however, as Ca 2+ currents and ROS production are mutually interconnected, it is difficult to distinguish the order in time between tip-localized ROS disruption and Ca 2+ current decrease [28]. Cytoplasmic Ca 2+ changes drastically affected the dynamics of AFs and MTs [13,28]. If AFs are not arranged correctly, this causes improper secretion and thus results in deeply altered cell wall deposition.…”
Section: Pollen Tube Growth and How It Is Impacted By Self-incompamentioning
confidence: 99%
“…In both apple and pear, the SI response certainly involves the cytoskeletal apparatus in a way that is not yet fully clarified. Yang and coworkers recently studied the timing of the events affecting the cytoskeleton during the SI response in apple; they demonstrated that AF depolymerization takes place within 6 minutes after SI induction, while pollen tube MTs are disrupted and form foci only 60 min after SI induction [13,51]. Therefore, MTs are likely to be a secondary target of the SI process but could also play more roles that are important during the SI response.…”
Section: The Tgase-cytoskeleton Interplay As a Crucial Player Of Tmentioning
confidence: 99%
See 2 more Smart Citations